TINGKAT KEPUASAN MAHASISWA TERHADAP KUALITAS MANAJEMEN DAN PELAYANAN LABORATORIUM BIOTEKNOLOGI PRODI BIOLOGI UNIVERSITAS PATTIMURA - Felsdian Imanuela Belegur; Lisa Kailola (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2018)
Achievement of laboratory learning objectives through practical and research is supported by the quality of management and laboratory services. Quality management and laboratory services that have not been optimal can be seen on the level of reality satisfaction and the expectations of laboratories users. This study aims to determine the level of students satisfaction on the quality of management and biotechnology laboratory services at Biology Department of Pattimura University Ambon. The result of the research can be used as an evaluation of the quality of laboratory services management and to act as consideration to design improvement of the management quality and biotechnology laboratories service. The sample in this research is the students of Biology Department of UNPATTI fourth, sixth and eighth semester. The data was obtained by observation and questionnaire distribution. The datas were analyzed using descriptive statistics, SERVQUAL, CSI and IPA method. The result of SERVQUAL method analysis showed 36% of the students were satisfied with the quality of biotechnology laboratory management but 64% of the students were not satisfied. 46% of the students were satisfied with the quality of biotechnology laboratory service but 54% of the students were not satisfied. The result of CSI method analysis showed that 73% student satisfaction level on the quality of biotechnology laboratory management has been fulfilled but 27% has not been fulfilled and 78% students satisfaction level on the service of biotechnology laboratory quality has been fulfilled and 22% has been not fulfilled yet. The result of IPA method analysis showed that 44% of the students considered the 18 quality attribute performance of biotechnology laboratory management should be maintained but 56% of the students considered that the performance of 12 attributes need to be improved. 48% of the students considered that the performance of 21 attributes biotechnology laboratory quality service must be maintained but 52% of students considered that the performance of 5 attributes need to be improved.